Pengaruh Hubungan Orang Tua dan Anak Remaja terhadap Pengetahuan Sikap Perilaku tentang Seks Bebas dan Narkoba - Muslichah, Miftakhul; Hilman, Orizaty (Universitas Muhammadiyah Yogyakarta, 2008)
Knowledge, attitude, behavior of free sex and napza of teenager in Indonesian needs serious attention of various circles of society. The knowledge derivedfrom family particulary from parent is more importance since family is the principal key in establishing attitude and behavior of teenager in socialization. In connection with this matter, the unhealthy reproduction behavior of teenager like having sexual intercourse in extra marital status or keep on changing partner freely, can result in the infection of sexual infection disease including HIV/AIDS, unwanted pregnancy, abortion, and use substance that lead into criminality. The objective of this study is to fine the influence relation between parents and teenager to knowledge, attitude, behavior of free sex and napza. This research is descriptive analytic and using quantitative method by cross sectional. The subject of this study were 115 respondent from the 2nd class in the students Senior High School Muhammadiyah Three Of Yogyakarta. Data collected from primary data with questionnaire method directly from the students. The data analysis used in the study was Corelation product moment of pearson. The result of the study showed that: there is significant relationship between perception of teenager with her parents to knowledge and attitude about free sex and napza. The knowledge of helth reproduction influenced the free sexual behavior of teenager.Pengetahuan, sikap, perilaku seks bebas dan napza remaja di Indonesia membutuhkan perhatian yang serius dari seluruh lapisan masyarakat. Pengetahuan yang diperoleh dari keluarga khususnya dari orang tua lebih penting lagi karena keluarga adalah kunci utama dalam menegakkan sikap dan perilaku remaja dalam bermasyarakat. Oleh karena itu, perilaku remaja dalam reproduksi yang tidak sehat seperti hubungan seks di luar nikah, berganti-ganti pasangan secara bebas, dapat berakibat penyakit infeksi seksual misalnya HIV/AIDS, hamil diluar nikah, aborsi, dan perilaku yang mengarah ke kriminalitas. Tujuan penelitian ini adalah untuk mengetahui hubungan antara orang tua dan remaja tentang pengetahuan, sikap dan perilaku seks bebas dan napza. Penelitian ini bersifat deskriptif analitik dengan metode kuantitatif secara cross sectional. Subyek penelitian adalah 115 siswa SMA Muhammadiyah 3 Yogyakarta kelas 2. Data yang dikumpulkan adalah data primer yang diperoleh langsung dari responden menggunakan metode kuesioner. Data dianaisis dengan uji korelasi product moment Pearson. Hasil penelitian menunjukkan bahwa ada hubungan yang bermakna antara persepsi remaja dengan orang tua